Visual Listening In: Extracting Brand Image Portrayed on Social Media - Liu, Liu; Dzyabura, Daria; Mizik, Natalie (Marketing Science, 2020)
A new approach for measuring consumer brand perceptions from consumer-created brand imagery via deep learning.